Pulmonary Embolism, Venous Thrombo-Embolism and Deep Vein Thrombosis associated with Hip Fracture in Elderly: A Critical Review on Diagnosis and Prevention (Bangladesh Critical Care Journal, 2026)
Deep Vein Thrombosis (DVT) of lower extremity and subsequent Venous Thrombo Embolism (VTE) often leads to Pulmonary Thrombo Embolism (PTE) otherwise called Pulmonary Embolism (PE). This review paper explores different international guidelines and various studies to discuss presentations of these three entities associated with hip fracture in elderly and ways to establish their presence with aim to prevent them. DVT, VTE, PE are consequences of hip fracture often suffered by elderly people who are prone to fall while attempting to walk. DVT may often be asymptomatic and PE may often present with occult signs and symptoms. As such both DVT and PE may often be missed by unsuspecting clinician. Patient undergoing hip fracture surgery (HFS) with untreated asymptomatic preoperative DVT or occult PE may suffer from severe PE resulting in shock and death. Elderly patient undergoing HFS may develop post-operative DVT and PE if proper prophylactic measures are not taken both before and after surgery. DVT can be diagnosed by D-dimer test and ultrasonography (USG). Multi Detector CT venography is more confirmatory than USG. However negative D-dimer test means absent DVT. CT Pulmonary Angiography (CTPA) is an effective diagnostic tool for PE. For prevention of DVT and VTE, pharmacological prophylaxis with low molecular weight heparin e.g. Enoxaparin is the drug of choice. For mechanical prophylaxis Intermittent Pneumatic Compression (IPC) device is the choice for the clinician provided USG shows no evidence of DVT in the lower extremity. In case of USG positive DVT, mechanical prophylaxis is contraindicated.Bangladesh Crit Care J March 2026; 14 (1): 45-51